Love is never silent - Petrie, Dorothea G.; Graviotto, Darlene; Sargent, Joseph (United States M. Rees Associates, 1985)
A young woman attempts to build her own life after years of serving as a link to the hearing world for her deaf parents.
VHS.
From the novel "In this sign" by Joanne Greenberg.
First 3 minutes of the film is distorted.
Mare Winningham, Phyllis Frelich, Ed Waterstreet, Fredric Lehne, Cloris Leachman, Sid Caesar.